Strengthening Geo-Maritime Resilience through Tourism Geopolitics in Indonesia - Anang Sutono; David Hind; Hari Ristanto; Muhammad Nur Ali Darajat; Muhammad Mas Multazam (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: This article examines the role of tourism as a soft power instrument in strengthening Indonesia's geo-maritime resilience in the Indo-Pacific through collaborative governance based on the Hexa Helix model that supports cultural diplomacy, civil presence, and maritime sovereignty. Design/Methodology/Approach: This study uses a qualitative approach through a systematic literature review that includes the identification, selection, synthesis, and analysis of literature, policies, and reports related to maritime development. The Hexa Helix model is applied to assess the involvement of academics, business actors, communities, government, media, and political institutions, with a focus on the Natuna, Sebatik, and Morotai loci, in understanding the role of tourism governance in strengthening non-military national resilience. Findings: The findings show that tourism makes an evident contribution to reinforcing geo-maritime resilience by increasing the welfare of coastal communities, promoting national identity, and boosting the state's presence in strategic maritime space. Collaborative governance has proven capable of synergising economic, social, cultural, and geopolitical values in a sustainable manner. Originality/Value: This research develops a conceptual framework that integrates soft power theory, the Hexa Helix governance model, and the Asta Gatra framework into a national resilience strategy. The study provides a new perspective for policymakers and academics on utilising tourism as a community-based, non-military approach to strengthen Indonesia's sovereignty and strategic position as the Global Maritime Axis.